Reduction of shrinkage on porkburger - Cruz, Ida L. (1984)
The best recipe for pork burger was selected among three tested recipes by sensory evaluation and was used in the succeeding phases of the study. In order to have the least shrinkage and cooking loss of porkburgers, it was found that two minutes cooking under medium heat was the most appropriate cooking time and temperature combination with the addition of 5% level of phosphate to the formulation. Freezing for two weeks gave no significant differences in sensory qualities; significant change was detected on the fourth week but the porkburgers were still acceptable; unacceptable and rancid samples were obtained on the sixth week. It was also found that storage in the freezer is directly proportional to cooking losses and shrinkage, and inversely proportional to water holding capacity and pH.